Fluorescent Fluoride Sensor Based on Indolizine Core Skeleton for Bioimaging. (30th October 2020) - Kim, Hyungi; Shin, Minchul; Kim, Eunha
Abstract : Schematic representation of fluoride anion sensing with Silyl‐KIz in live cell